Low anterior resection syndrome score among Nepalese population undergoing lower anterior resection for rectal carcinoma - Maharjan, Dhiresh Kumar; Acharya, SC; Thapa, PB (Journal of Kathmandu Medical College, 2018)
Background: With more sphincters preserving surgery being performed for distal rectal cancer, these have been associated with clusters of symptoms experienced by the patient after reversal of diverting ileostomy collectively known as low anterior resection syndrome.Objective: Our objective is to know incidence of Lower Anterior Resection (LAR) syndrome in different phase of time in our context using low anterior resection symptom score translate in Nepali language.Methodology: This is an observational descriptive study conducted at Department of Surgery, Kathmandu Medical College and Department of Clinical Oncology, Bir Hospital, Kathmandu from Jan 2015 till Jan 2017. All patients who had undergone low and ultra low anterior resection for middle and low rectal cancer respectively after a long course of neo adjuvant concurrent chemo radiotherapy, having undergone a reversal of diverting ileostomy after 6 weeks of primary surgery were included. A Nepalese version of low anterior resection score was developed after translation from English and scoring was done on 30th day, at the end of 6 months and 1 year postoperative following reversal of ileostomy.Results: Out of 43 consecutive patient 100 % of patients had features of major low anterior resection syndrome during 30 days of ileostomy reversal. However, 46.5% patient showed major low anterior resection syndrome during 6 months of follow up and that decreased to 34.9% showed major LAR syndrome upon one year of follow up.Conclusions: The Low anterior resection syndrome score converted in Nepali language is feasible to use and helps in comparing the functional results of reconstruction after low or ultralow anterior resection and our study have shown improvement in score with time. Journal of Kathmandu Medical College,Vol. 7, No. 2, Issue 24, Apr.-Jun., 2018, page: 59-63